2018
DOI: 10.1039/c7cs00735c
|View full text |Cite
|
Sign up to set email alerts
|

Peptide supramolecular materials for therapeutics

Abstract: Supramolecular assembly of peptide-based monomers into nanostructures offers many promising applications in advanced therapies. In this Tutorial Review, we introduce molecular designs to control the structure and potential biological function of supramolecular assemblies. An emphasis is placed on peptide-based supramolecular nanostructures that are intentionally designed to signal cells, either directly through the incorporation of amino acid sequences that activate receptors or indirectly by recruiting native… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
190
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 229 publications
(190 citation statements)
references
References 50 publications
(49 reference statements)
0
190
0
Order By: Relevance
“…Meanwhile, the delivery of therapeutic peptides is known to be challenging concerning their short half-life due to the rapid proteolytic degradation and short circulation time due to the low molecular weight. 23,24 These could be potentially overcome by covalently grafting oligopeptides at the side chains of peptide brush polymers, 25 or integrating them onto peptide amphiphiles 26 or PEGylation 27 .…”
Section: Design Of Oligopeptide Inhibitormentioning
confidence: 99%
“…Meanwhile, the delivery of therapeutic peptides is known to be challenging concerning their short half-life due to the rapid proteolytic degradation and short circulation time due to the low molecular weight. 23,24 These could be potentially overcome by covalently grafting oligopeptides at the side chains of peptide brush polymers, 25 or integrating them onto peptide amphiphiles 26 or PEGylation 27 .…”
Section: Design Of Oligopeptide Inhibitormentioning
confidence: 99%
“…The attachment of lipophilic moieties to hydrophilic drug molecules enhances the bioavailability of the therapeutic agents . Despite that various peptides have been modified by anchoring of hydrophobic acyl chains (lipidated peptides), the resulting structures have scarcely been composed of neuroprotective molecules . At variance, extensive research has been reported on self‐assembly of antimicrobial and anticancer peptides and the destabilization of lipid membranes …”
Section: Introductionmentioning
confidence: 99%
“…Short synthetic peptides derived from ECM proteins retain the integrin-binding function, thus are attractive in the design of materials. For example, the Stupp group has developed bioactive peptide amphiphiles (PA) for regenerative medicine applications (Boekhoven and Stupp, 2014;Hendricks et al, 2017;Sato et al, 2018). The RGDS sequence has been attached to PA to induce integrin-mediated adhesion, spreading or migration of fibroblasts, breast cancer cells, and bone marrow mononuclear cells in vitro (Storrie et al, 2007;Webber et al, 2010;Zhou et al, 2019).…”
Section: Interactions Of Ecm With Cell Receptorsmentioning
confidence: 99%